Functionalized carbon-based nanomaterials and quantum dots with antibacterial activity: a review. Issue 1 (2nd January 2021) - Alavi, Mehran; Jabari, Erfan; Jabbari, Esmaiel
ABSTRACT: Introduction: Emergence of antibiotic resistance in bacteria is a complicated issue, especially when treating infectious immunodeficiency related diseases. In recent years, when compared to bulk materials, nanomaterials (NMs) with specific antibacterial activities have played a novel role in treating bacterial infections. Among NMs, quantum dots (QDs), specifically carbon containing QDs including graphene oxide QD (GOQD), graphene QD (GQD), and carbon QD (CQD), have demonstrated bacteriostatic and bactericidal activities via photodynamic (PD) effects against antibiotic resistant bacteria under a certain wavelength of light. Area covered: In this mini-review, recent advances and challenges related to antibacterial and biocompatibility activities of modified GQD, GOQD, CQD, and carbon nanotubes (CNTs) are discussed. Expert opinion: Lower stability and biocompatibility of QDs at higher doses in physiological conditions are major disadvantages. In this regard, functionalization of these QDs can result in appropriate bactericidal, biocompatibility, and biodegradability properties. In the case of CNTs including single-wall carbon nanotube (SWCNTs) and multiwall carbon nanotube (MWCNTs), aspect ratio (AR) is a determinant factor for the antibacterial value. Moreover, MWCNTs show a lower antibacterial ability compared to SWCNTs, which can be improved by modifying their surface.